2009
DOI: 10.1007/s00330-009-1454-y
|View full text |Cite
|
Sign up to set email alerts
|

Acute myocarditis in a rat model: late gadolinium enhancement with histopathological correlation

Abstract: The aim of the current study was to use an established animal model of autoimmune myocarditis and to judge the ability of cardiovascular MRI (CMR) in quantitatively measuring the extent of myocardial involvement compared with histopathological measurement of severity and extent. Experimental autoimmune myocarditis (EAM) was induced in 10 male Lewis rats. On day 21, all animals were investigated by CMR to measure the extent of late gadolinium enhancement (LGE). Subsequently, histopathological evaluation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 24 publications
6
21
0
Order By: Relevance
“…rats on Day 21 after the induction of EAM, mapped the distribution of LGE using a seven-segment model of the LV, and reported that LGE was located mainly in the anterior and lateral LV walls, and was correlated with histopathology findings. 3,4 In the present study, CMR accurately identified the location and the extent of myocardial damage, which corresponded with the histopathological picture of myocarditis. These findings also correlate with typical findings in humans with myocarditis, showing a subepicardial distribution of LGE mainly in basal and mid-infero-lateral segments.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…rats on Day 21 after the induction of EAM, mapped the distribution of LGE using a seven-segment model of the LV, and reported that LGE was located mainly in the anterior and lateral LV walls, and was correlated with histopathology findings. 3,4 In the present study, CMR accurately identified the location and the extent of myocardial damage, which corresponded with the histopathological picture of myocarditis. These findings also correlate with typical findings in humans with myocarditis, showing a subepicardial distribution of LGE mainly in basal and mid-infero-lateral segments.…”
Section: Discussionsupporting
confidence: 67%
“…Significantly, the present study expands upon previous studies by providing new findings on myocarditis in a rat model. 3,4 First, in addition to…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, assessment of LGE is a well established CMR parameter in the evaluation of heart failure in the setting of coronary artery disease, myocarditis, and various cardiomyopathies [21][22][23][24][25][26][27]35]. It is important to recognize that LGE is not specific but can reflect myocardial necrosis, non-ischemic fibrosis, and ischemic scars.…”
Section: Discussionmentioning
confidence: 99%
“…Small animal imaging is an important tool for the study of cardiovascular diseases. Techniques routinely used in clinical CMR, such as late gadolinium enhancement (LGE) cannot easily be transferred to small animal CMR due to the animals' high heart rates; but could already be shown 11 . The small animal Look-Locker inversion recovery (SALLI) approach generates multi-modal image data sets allowing for the comprehensive assessment of both cardiac function and morphology (Figures 1 and 3).…”
Section: Introductionmentioning
confidence: 99%